The Effectiveness of Group Activity Therapy: Cognitive Stimulation on the Ability to Control Hallucinations in Schizophrenia Patients - Qarimah, Siti Nurafifah; Fahmi Adha, Mohd. Rizal; Mulyadi, Andi; Rizki, Muhammad Reza; Rufli, Arza; Fazlylawati, Ellyza; Lumbantoruan, Vivi Pretty; Pagan, Sabran Hadi (Lembaga Teewan Journal Solutions, 2026)
Schizophrenia is a severe mental disorder characterized by disturbances in reality testing, where auditory hallucinations represent the most dominant clinical manifestation. Ineffective coping mechanism for hallucinations often triggers violent behavior. Group Activity Therapy (GAT) for perceptual stimulation is a nursing intervention designed to train patients to manage hallucinations through interactive group dynamics. This study aimed to evaluate the effectiveness of GAT perceptual stimulation on the ability to control hallucinations among schizophrenic inpatients. A quasi-experimental design with a pre-post-test with control group approach was employed. Thirty respondents were selected through purposive sampling and divided into an intervention group (n=15) and a control group (n=15). The intervention group received 5 sessions of GAT, while the control group received standard individual nursing care. Data were collected using a standardized observation checklist and analyzed using Paired and Independent T-Tests. The results showed a significant increase in the mean score of hallucination control ability in the intervention group post-test (p=0.001), whereas the control group showed no significant change (p=0.112). Inter-group analysis revealed a significant difference between the two groups post-intervention (p=0.002). This study concludes that GAT perceptual stimulation is highly effective in improving both cognitive and psychomotor abilities of schizophrenic patients in controlling auditory hallucinations.